Pemilihan Bahasa dalam Masyarakat Tutur Konjo di Sinjai - , Herawati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study about âThe Language Choice in The Konjo Speech Community in Sinjaiâ describes the language situation in Sinjai which includes the general description of the languages used daily. It also describes the forms of the languages and examines the factors governing the language choice while attempting to correlate such factors with domains and role relations. By using field research method, that is by participantâs observation which is combined with the observerâs paradox technique, the data were collected from daily speech events in the various domains. The data are then classified according to the types, patterns, and factors that determine the language usage. There are four languages (BK, DBS, DMB, and BI) used daily in the speech community. They are allocated to different social functions and contexts, that is known as polyglossia. In situationswhere the social context favors multiple interethnics contacts, however, some speakers who identify with minority ethnic groups may choose to incorporate features from a dominant variety into their speech. Multilinguals show varying degrees of proficiency in the languages they choose in various domains. Consequently, there are several patterns of language choice, namely, in the family domain are: BK + BK, BI + DMB + BK, and DMB + BK